The Influence of the Presence of Art on Social Cohesion during Covid 19 - Iuliana COMAN (Communications of International Proceedings, 2020)
The crisis generated by the Covid-19 pandemic brought major changes in the behavior of the society, on the freedom of movement, on the organization of events, on the program of schools and universities. The aim of this paper is the evaluation of the changes manifested in the behavior of art consumers with an accent on the influences manifested by art upon the social cohesion during the Covid-19 pandemic. The research considers macroeconomic indicators provided by the National Institute of Statistics, Eurostat, and a survey conducted in the first week of May 2020, during the Covid-19 crisis. The purpose of the survey was to analyses art consumer behavior during this pandemic, the presence of art in the lives of respondents, and the influence that art has on the life of society. The sample of the survey included 200 persons with high education in the South of Romania, being defined using demographic sampling rates. The results showed that art continued to be present in the life of society and participate in supporting the passage of this period, continuing to participate in the consolidation of the community.
Keywords: Art; Society; Community; Influences; Covid-19.